Antibacterial and cytotoxic effect of honey mediated copper nanoparticles synthesized using ultrasonic assistance - Nur Afini, I.; Shameli, Kamyar; Wong, Magdelyn Mei Theing *; Teow, Sin Yeang *; Chew, Jactty *; Siti Nur Amalina, M. S. (Elsevier, 2019)
In this study, a comparative study of effect using honey on copper nanoparticles (Cu-NPs) via simple, environmentally friendly process and inexpensive route was reported. Honey and ascorbic acid act as stabilizing and reducing agents with the assistance of sonochemical method. The products were characterized using UV–visible (UV–vis) spectroscopy, X-Ray Diffraction (XRD), High-Resolution Transmission Electron Microscopy (HRTEM), Field-Emission Scanning Electron Microscopy (FESEM) and Fourier Transform Infrared (FTIR) spectroscopy. The reddish brown colour demonstrated the formation of Cu-NPs and UV–visible proved the plasmon resonance of Cu-NPs. XRD also confirmed a highly pure Cu-NPs obtained with absence of copper oxide in which the structure is crystalline. The spherical size of the Cu-NPs was acquire in the presence of honey which is 3.68 ± 0.78 nm with narrow particle distribution. The antibacterial activity was seen against gram-positive and gram-negative bacteria which are Enterococcus faecalis (E. faecalis) and Escherichia coli (E. coli). At higher concentration of Cu-NPs, they were more effective in killing both bacteria. The Cu-NPs without and with honey exhibited toxicities toward normal and cancerous cells. However, Cu-NPs without honey showed more potent killing activity against normal and cancer cells.